Characterization and Quantification of Thermal Load during Wort Boiling - De Schutter, David P.; De Meester, Marie-Rose; Daan Saison, Daan Saison; Delvaux, Filip; Derdelinckx, Guy; Rock, Jean-Marie; Neven, Hedwig; Delvaux, Freddy R. (BrewingScience, 2008)
Thermal load is often considered as a vague and obscure burden for brewers. In order to clarify the concept of thermal load, this paper aimed to characterize and quantify thermal load during wort boiling. Thermal processing of wort was found to cause the accumulation of Maillard intermediates, which might lead to the generation of off-flavours during beer ageing. The amount of intermediates could be quantified in terms of HMF-equivalents. A part of these intermediates was reduced by yeast during fermentation. The remaining non-reducible intermediates in beer can therefore be considered as the chemical memory of thermal load on wort.In order to quantify thermal load in wort, the kinetic behaviour was examined and a pseudo 0th order kinetics was established. The quantification of thermal load was then captured in a formula, which consisted of two terms. The first is a specific wort term, which evaluates the susceptibility of a particular wort to applied thermal load. This tool could be used by every brewer to predict the effect of boiling process changes on the wort. In addition, a boiling system term was created. Although the latter term is highly theoretical, it provides insights in the impact of differences in boiling intensity on thermal load of wort.